2002
DOI: 10.1111/j.1741-3737.2002.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Teen Sexual Behavior: Applicability of the Theory of Reasoned Action

Abstract: ࡗ Teen Sexual Behavior: Applicability of the Theory of Reasoned ActionWe examined the utility of the theory of reasoned action for predicting sexual intercourse among teenagers and determined whether it holds for both genders and for those with and without prior sexual experience. The data include 749 students who were in 9th-11th grades when the predictors were measured and in 10th-12th grades when sexual intercourse was assessed. About half (53%) were girls, about half (48%) were non-Hispanic European Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 45 publications
5
91
0
8
Order By: Relevance
“…In terms of both fertility intentions and behaviour, women with one child displayed greater variability compared to childless women (who were more likely to intend to have a child or to make the actual parity progression) and to women with two or more children (who were unlikely to do either). For the overall sample, as well as for women at every parity, fertility intentions were good predictors of actual births, which is consistent with the literature (e.g., Vinokur-Kaplan 1978;Gillmore et al 2002). Moreover, among women who intended to have children, those with one child were the most likely to make parity progression, as was found in Europe (Berrington 2004;Toulemon and Testa 2005) and the United States (Schoen et al 1999).…”
Section: Resultssupporting
confidence: 77%
“…In terms of both fertility intentions and behaviour, women with one child displayed greater variability compared to childless women (who were more likely to intend to have a child or to make the actual parity progression) and to women with two or more children (who were unlikely to do either). For the overall sample, as well as for women at every parity, fertility intentions were good predictors of actual births, which is consistent with the literature (e.g., Vinokur-Kaplan 1978;Gillmore et al 2002). Moreover, among women who intended to have children, those with one child were the most likely to make parity progression, as was found in Europe (Berrington 2004;Toulemon and Testa 2005) and the United States (Schoen et al 1999).…”
Section: Resultssupporting
confidence: 77%
“…Niat untuk berhubungan seks pranikah berhubungan dengan inisiasi hubungan seksual atau hubungan seksual dan terlibat di dalam sejumlah situasi-situasi progresif yang berisiko. 2,21,22 Niat secara langsung dipengaruhi oleh sikap, tekanan normatif, dan personal agency. Kemungkinan niat tidak berhubungan dengan perilaku seks pranikah remaja di Bali disebabkan karena pengaruh dari tekanan normatif serta personal agency kurang kuat.…”
Section: Pembahasanunclassified
“…For example, studies have revealed that at older ages, that is, between 16 to 17 years, boys and girls are equally likely to engage in sex, even though boys are more likely than girls to have sex at an early age (Gillmore 2002;Upchurch et al 1999, Nahom et al 2001. In a study by the National Department of Health, it was found that six percent of young women (15 -24 years) reported having had sex by the age of 15, compared with 12 percent of young men.…”
Section: Literature Reviewmentioning
confidence: 99%